2015
DOI: 10.1080/1068316x.2014.999063
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of group offending on behavioural similarity in serial robbery

Abstract: Behavioural case linkage assumes that offenders behave in a similar way across their crimes. However, group offending could impact on behavioural similarity. This study uses robbery data from two police forces to test this by comparing the behavioural similarity of pairs of lone offences (LL), pairs of group offences (GG) and pairs of offences where one crime was committed alone and the other in a group (GL). Behavioural similarity was measured using Jaccard's coefficients. Kruskal-Wallis tests were used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Whereas CCA is concerned with structured queries within large databases such as ViCLAS to find similar cases [1], CLA is a process where a behavioural investigative advisor (BIA) examines a smaller number of two or more offences with regard to their linkage potential. The empirical crime linkage literature has rather focussed on CCA scenarios and amassed a substantial body of research (Burrell et al, 2012;Davies et al, 2012;Ellingwood et al, 2013;Tonkin et al, 2011a;Tonkin et al, 2011b;Salo et al, 2012;Santtila et al, 2005;Santtila et al, 2008;Woodhams and Labuschagne, 2011;Woodhams and Toye, 2007) that has demonstrated two main findings: First, crime linkage is a worthwhile endeavour as large scale studies such as Woodhams et al (2019b) have proved that the theoretical assumptions of consistency and distinctiveness do hold up in international samples of serial sexual assaults. Second, various statistical algorithms do perform objectively well in linking crimes committed by the same offender.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas CCA is concerned with structured queries within large databases such as ViCLAS to find similar cases [1], CLA is a process where a behavioural investigative advisor (BIA) examines a smaller number of two or more offences with regard to their linkage potential. The empirical crime linkage literature has rather focussed on CCA scenarios and amassed a substantial body of research (Burrell et al, 2012;Davies et al, 2012;Ellingwood et al, 2013;Tonkin et al, 2011a;Tonkin et al, 2011b;Salo et al, 2012;Santtila et al, 2005;Santtila et al, 2008;Woodhams and Labuschagne, 2011;Woodhams and Toye, 2007) that has demonstrated two main findings: First, crime linkage is a worthwhile endeavour as large scale studies such as Woodhams et al (2019b) have proved that the theoretical assumptions of consistency and distinctiveness do hold up in international samples of serial sexual assaults. Second, various statistical algorithms do perform objectively well in linking crimes committed by the same offender.…”
Section: Introductionmentioning
confidence: 99%
“…Serial cases have always been the focus of research by the public security organs of various countries, and the research dimensions are diverse. Burrell, Bull, Bond, and Herrington (2015) measured behavioural similarity using Jaccard's coefficients and used Kruskal-Wallis tests to examine the differences between the linked samples. Campobasso et al (2009) discussed the suspect's motivation, mental health, childhood experiences and other issues in an in-depth study of 15 murder cases of older women over the age of 70.…”
mentioning
confidence: 99%
“…Crime linkage researchers typically control for the impact of prolific offenders by selecting a constant number of crimes per offender (e.g., Bennell & Canter, 2002;Burrell, Bull, Bond, & Harrington, 2015;Markson et al, 2010;Tonkin, Woodhams, et al, 2012).…”
Section: Controlling the Impact Of Prolific Offenders A Common And mentioning
confidence: 99%
“…As shown earlier in Table 4, the median number of days between unlinked crime pairs was 1,527 days. Most linking studies examining temporal proximity as a predictor have sampled crimes over a shorter timeframe, ranging from 1 to 5 years (e.g., Burrell et al, 2012Burrell et al, , 2015Davies, Tonkin, Bull, & Bond, 2012;Markson et al, 2010;Tonkin, Woodhams, Bull, Bond, & Palmer, 2011;Tonkin & Woodhams, 2015). 39 The median number of days between unlinked crime pairs in these studies is 39 The exception to this is Tonkin, Santtila, et al (2012), where the sample was comprised of Finnish residential burglaries committed between 1990 and 2001; however, the median number of days between crimes for linked pairs and unlinked pairs was not reported in this study.…”
Section: Phase 2: Developing and Evaluating The Main Effects Linking mentioning
confidence: 99%
See 1 more Smart Citation